2021
DOI: 10.1186/s13048-021-00927-5
|View full text |Cite
|
Sign up to set email alerts
|

Ovarian reserve in nigerian women with sickle cell anaemia: a cross- sectional study

Abstract: Introduction Sickle cell disease is the most common monogenetic disorder worldwide. There have been reports of endocrine dysfunction and gonadal failure among affected individuals, especially in males. The findings on ovarian reserve and failure in women with sickle anaemia have been inconsistent. Aim and objective The aim of this study was to determine and compare the ovarian reserve of Nigerian women with and without sickle cell anaemia attending… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 19 publications
0
11
0
Order By: Relevance
“…Three studies have demonstrated normal anti-müllerian hormone (AMH) levels in untreated adolescent and young adults with SCD ( 32 34 ). However, women with SCD experience a more rapid decline in ovarian reserve, with lower levels of AMH than age matched controls ( 33 , 35 , 36 ). Females with SCD develop diminished ovarian reserve (DOR) at younger ages (25-30 years) than age-matched women ( 33 , 34 ).…”
Section: Impact Of Hemoglobinopathies On Fertilitymentioning
confidence: 99%
“…Three studies have demonstrated normal anti-müllerian hormone (AMH) levels in untreated adolescent and young adults with SCD ( 32 34 ). However, women with SCD experience a more rapid decline in ovarian reserve, with lower levels of AMH than age matched controls ( 33 , 35 , 36 ). Females with SCD develop diminished ovarian reserve (DOR) at younger ages (25-30 years) than age-matched women ( 33 , 34 ).…”
Section: Impact Of Hemoglobinopathies On Fertilitymentioning
confidence: 99%
“…Age-based thresh olds for infer til ity diag no sis may not apply to women with SCD, who have a sharper tra jec tory of decline in ovar ian reserve. [18][19][20][21][22] At Johns Hopkins, we offer repro duc tive endo cri nology and infer til ity (REI) spe cial ist con sul ta tion to women who have attempted to con ceive for 6 months or lon ger. Helping patients know when to seek care can help with timely REI referral; rec og nized bar ri ers to infer til ity care make atten tion to referral tim ing espe cially impor tant.…”
Section: Learning Objec Tivesmentioning
confidence: 99%
“…25 This helps explain why age-asso ci ated decline in ovar ian reserve appears to be accel er ated in women with SCD (Figure 2). [18][19][20][21] In a small study of women with sickle cell ane mia (SCA), men o pause occurred ear lier than the gen eral pop u la tion. 26 This might be expected in a dis ease asso ci ated with accel er ated aging and sup ports the hypoth e sis that women with SCD have a narrower repro duc tive win dow than unaf fected women.…”
Section: Case (Con Tin Ued)mentioning
confidence: 99%
“…[7][8][9] Specifically, Garba et al found that after controlling for age and body mass index, ovarian reserve, as measured by serum anti-Mullerian hormone (AMH), was lower among those with HbSS versus HbAA. 10 Treatment for SCD may also impact fertility among women, with data to support that younger women of ages 10-24 years treated with hydroxyurea had higher rates of DOR. 11 Among males with SCD, evidence indicates that factors contributing to infertility include delayed puberty, low testosterone, and sperm abnormalities 12 due to testicular dysfunction.…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, Garba et al. found that after controlling for age and body mass index, ovarian reserve, as measured by serum anti‐Mullerian hormone (AMH), was lower among those with HbSS versus HbAA 10 . Treatment for SCD may also impact fertility among women, with data to support that younger women of ages 10–24 years treated with hydroxyurea had higher rates of DOR 11 .…”
Section: Introductionmentioning
confidence: 99%